Deposit insurance system and its role in financial security for the period (2010-2018) Study the experiences of Selected countries with reference to Iraq - Mejbel, Rusel Omer; Dawood, Samir Suham (Journal of Economics and Administrative Sciences, 2020)
Founding a System to secure deposits and protecting the depositors is considered one of the important and exchanged subjects out there in the banking system/field in Iraq at the current time, and the reason behind the exchange and spread of this subject is due to the financial crisis of which the banking sector is suffering from and the stumbling of many banks, those factors have had led to the insecurity of the depositors and their mistrust towards banks, thus, it is necessary to create a system to secure deposits in which depositors would be compensated for the losses caused by the banks' failures. in addition, it could be a countermeasure system which maintains the banking stability, protects the rights of depositors and gains/win their trust in the banking system., considering the stability of the banking system would positively reflect upon the safety of the banks' financial branches and avoiding its' exposure to failure. In addition to that, this system protection to the rights of the depositors is considered an indirect assurance for the stability of the banking deposits activities through strengthening trust in the banking system and support the financial security of the depositors, that trust can affect the increase of deposits volume in its' various forms and increasing the banking transactions volume. The achievement of what we've addressed and detailed prior to this is depending on founding the right platform which represents the readiness of the banking sector to create a system to secure banking deposits.